Pengaruh Pelatihan dan Motivasi Kerja Terhadap Kinerja Karyawan pada PT. Andika Rajawali Indoserpis Kota Depok - Sheviana Zulfa Awaliya; Isnurrini Hidayat Susilowati (Jurnal Manajemen dan Ekonomi Kreatif, 2024)
This research aims to see the effect of training and work motivation on employee performance partially and simultaneously. The sample taken for data collection was the entire population in the company, namely 66 respondents. This research is quantitative research by testing hypotheses using SPSS 25. The results of the t test research (partial) on the training variable show t count 3.235 ≥ t table 1.669 and a significant value of 0.002 ≤ 0.05, meaning that the training variable partially and significantly influences employee performance in PT Andika Rajawali Indoserpis Depok City. The results of the t test research (partial) on the work motivation variable show that the t count is 4,599 ≥ t table 1,669 and the significant value is 0.000 ≤ 0.05, meaning that the work motivation variable partially and significantly influences employee performance at PT Andika Rajawali Indoserpis, Depok City. Based on the SPSS 25 output results, the results of the F test research (simultaneous) show that the calculated F value is 43.124 ≥ F table 3.14 and the significant value is 0.000 ≤ 0.05. So it can be concluded that training (X1) and work motivation (X2) together have a significant effect on employee performance (Y).